PERENCANAAN RAINWATER HARVESTING SYSTEM SMA NEGERI 1 TAEBENU, NUSA TENGGARA TIMUR - Sonbay, Jachin Alpin; Bees, Azarya; Nomnafa, Ardin M; Muji, Dionisius P; Klakik, Evang Edito (Eternitas: Jurnal Teknik Sipil, 2024)
Rainwater Harvesting System (RWHS) is a simple concept for utilizing water resources, by collecting rainwater that falls in the roof and channeling it into a reservoir. Non domestic water needs in school buildings are needed in large quantities considering the large number of water users. With the RWHS concept, it is hoped that it can provide an alternative solution for using rainwater at SMA Negeri 1 Taebenu. Basen on the results of the water balance analysis at SMA Negeri 1 Taebenu, the water deficit was greatest in Juli at 0,61 liters/s. Based on these values, 2 rainwater storage tanks are planned with a capacity of 4,5 m3 each with dimensions of 1,5 x 1,5 x 2 meters. The storage tank is designed to be below groung level due to limited land. Rainwater is only used for bathroom purposes and watering plants, so the design of the reservoir is made simple, just using a dirt filter in the gutter to dispel dirt carried from the roof into the tank.